DIMENSI HUMANISME DALAM KARYA SASTRA AL-MANFALÛTHÎ (SEBUAH KRITIK SASTRA HUMANIS ATAS KARYANYA “AL-NADHARA ̂T”) - Syarifuddin Syarifuddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Musthafa Luthfi Al- Manfaluthi (1876-1924) is a famous Arabian poet from Egypt who has given a real contribution and influence for development of modern Arab prose specifically and Arab’s literature generally. The intellectual maturity and his writing has been a foundation of his emotional awareness toward humanity in his writing Al Nadharat, such as a commitment to preserve traditions and community’s values, commitment to perform a social reform and an advocation for people in need. His call to defend people under repressive authority and poor people is based on cultural treasure of Arab. This article aims to discuss the background of education, life, literature personality, social and writings of Al Manfaluthi and also the characteristic of his writing Al Nadharat from its language structure and thoughts and method of esthetical expression, and also to discover humanism dimension instituted in his writing, which came from Egypt society during that time.